Air quality protection behaviour and stock returns of public companies: Sectoral aspects - Maksim S. Maramygin; Natalya B. Boldyreva; Lyudmila G. Reshetnikova (Управленец)
In the new economic reality, air quality protection behaviour of companies remains a burning issue shifting the em phasis towards saving human life and health. The article explores the relationship between the air quality protection behav iour of public companies and stock returns in different economic sectors. The research methodology is based on environmental management theory, financial management theory, and stakeholder theory. The analytical procedures performed on the data involved cross-sectoral economic analysis and econometric analysis. Empirical data are retrieved from the Federal State Statistics Service (Rosstat) and the Moscow Exchange and cover statistics on 45 public joint-stock companies (PAOs) from five sectors of the economy for the period of 2014–2022. Cross-sectoral economic analysis has shown that investors lack interest in PAOs’ air quality protection behaviour and invariably favour companies from the sectoral indices paying higher dividends compared to the Moscow Exchange, such as Chemicals and Petrochemicals, Metals and Mining, Oil and Gas. By integrating air quality protection factors into the Fama-French-Carhart model through econometric modelling, we estimated the dependence of returns of indus try portfolios on these factors and classical risk premiums. The study demonstrates a positive impact of market premium and size premium on returns of industry portfolios. No statistically significant impact of air quality protection factors on stock returns was found. Our empirical findings confirm that businesses are poorly motivated to take air environment protection measures and air pollution-reducing behaviour should be encouraged at the state level.